A randomised trial on the effect of anti-platelet therapy on the systemic inflammatory response in human endotoxaemia - Kiers, Dorien; van der Heijden, Wouter A.; van Ede, Lisa; Gerretsen, Jelle; de Mast, Quirijn; van der Ven, Andre J.; el Messaoudi, Saloua; Rongen, Gerard A.; Gomes, Marc; Kox, Matthijs; Pickkers, Peter; Riksen, Niels P. (Thrombosis and Haemostasis, 2017)
The use of acetylsalicylic acid (ASA) is associated with improved outcome in patients with sepsis, and P2Y12 inhibitors have been suggested to also have immunomodulatory effects. Therefore, we evaluated the effects of clinically relevant combinations of antiplatelet therapy on the immune response in experimental endotoxaemia in humans in vivo. Forty healthy subjects were randomised to seven days of placebo, placebo with ASA, ticagrelor and ASA, or clopidogrel and ASA treatment. Systemic inflammation was elicited at day seven by intravenous administration of Escherichia coli endotoxin. ASA treatment profoundly augmented the plasma concentration of pro-inflammatory cytokines, but did not affect anti-inflammatory cytokines. Addition of either P2Y12 antagonist to ASA did not affect any of the circulating cytokines, except for an attenuation of the ASA-induced increase in TNFα by ticagrelor. Systemic inflammation increased plasma adenosine, without differences between groups, and although P2Y12 inhibition impaired platelet reactivity, there was no correlation with cytokine responses.Note: This work was performed at the Radboud University Medical Center, Nijmegen, The Netherlands.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Acetylsalicylic acid; ticagrelor; clopidogrel; endotoxaemia; platelet inhibition